A philosophical critique of the UK's National Institute for Health and Care Excellence guideline 'Palliative care for adults: strong opioids for pain relief'. Issue 3 (August 2018) - Fearon, David; Hughes, Sean; Brearley, Sarah G
The National Institute for Health and Care Excellence (NICE) promotes evidence-based medicine throughout contemporary health care. Its guidelines are employed in the United Kingdom and elsewhere, influencing the type and quality of health care provided. NICE considers a range of evidence in the process of creating guidelines; however, the research accepted as evidence greatly relies on positivist methodologies. At times, it is unnecessarily restricted to quantitative methods of data collection. Using the Clinical Guideline 140, opioids in palliative care, as an example, it is demonstrated that the research accepted as evidence is unable to provide answers to complex problems. In addition, several inherent biases are discussed, such as age inequality and pharmaceutical company influence. In order to provide coherent and useful guidelines relevant to complex problems in a real world setting, NICE must move away from focusing on data from randomised controlled trials. Its epistemological foundation must be questioned, paving the way for alternative research paradigms to be considered as evidence and thereby enriching subsequent guidelines.